Estudo de estabilidade acelerada aplicado ao tempo de vida de prateleira - Marini, David Giovani (Universidade Federal de São Carlos, 2022)
The present accelerated stability study aims to simulate the expiration date of a test to detect Chagas disease, subjecting it to temperatures above its storage temperature (5.0°C), to accelerate its degradation speed. The study allows verifying whether the functional characteristic of the test maintains the levels acceptable to the market, according to the requirements of ANVISA (National Health Surveillance Agency), in matters of quality and product safety. Through the experimental values of optical density as a function of the time collected, it was possible to apply two distinct methods to determine the kinetic constant (k), which are: the method of integral analysis and the objective function with data dispersion analysis. From the values of the kinetic constants and their temperatures, it is possible to determine the activation energy (Eatv) for the reactional complex of the Chagas test, whose value was 48.60 kJ/mol, characteristic for health products, in addition to determining the acceleration factor α10, which for the test considered was 1.32, less than that established by ANVISA, which determines a value of α10 equal to 2.0. In this sense, through the accelerated stability study it was concluded that the most advantageous scenario for this test is to submit it at room temperature of 25.0°C for a period of approximately 133 days, performing regular tests during this time interval, evaluating it in terms of quality and safety. If so, the records should be forwarded to ANVISA for registration and subsequent marketing.
Accelerated stability study applied to shelf life
Keywords: Estabilidade acelerada; Tempo de vida de prateleira; Constante de velocidade específica; Accelerated stability; Shelf life; Specific speed constant; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA; 9. Indústria, Inovação e Infraestrutura; 12. Consumo e Produção Responsáveis